PELATIHAN PEMBUATAN PUPUK ORGANIK DARI LIMBAH SAYURAN DI DESA PESANGGRAHAN KOTA BATU - Mohammad Istnaeny Hudha (Dharma: Jurnal Pengabdian Masyarakat, 2021)
Pesanggrahan village is located under Panderman mountain, Batu city. Most of its residents are farmers and ranchers and some are entrepreneurs. The most dominant numbers are farmers and cattle breeders. To accommodate the activities of farmers and breeders, the "Urip Sejahtera" Farmer Group was formed. Along with the development of increasingly advanced agriculture, the use of chemical fertilizers is increasing. This of course has a serious impact on soil conditions. So that an action is needed to find a solution to improve the nutrients in agricultural land.Vegetable waste generated from agricultural activities is an unsolved problem. The waste produced by humans consists of organic and inorganic waste. Organic waste that is produced from vegetable waste is generally thrown away and can cause an unpleasant aroma, besides that it will also trigger the growth of disease-causing microorganisms. The goal to be achieved from the training activities for making organic fertilizer from vegetable waste is to provide information, knowledge and to raise public awareness of the importance of efficient waste management, so that the people of Pesanggrahan Village, Batu City do not carelessly dispose of vegetable waste. The method applied in this activity is to present the material then carry out direct practice to make organic fertilizer. Then do an evaluation of the resulting product..Keywords: Vegetable Waste, Fermentation, Organic Fertilizer